TEM observation of inorganic substances distributed in gel materials for medical devices using ultra-thin cryosectioning. (10th July 2020) - Ito, Eri; Takase, Hiroshi; Yamamoto, Katsuhiro
Abstract: In this study, a method was developed for examining the distribution pattern of inorganic substances dispersed in hydrogel-filled medical devices. Transmission electron microscopy (TEM) using ultra-thin cryosectioning (owing to hydrogel's water content) was performed on contact lenses with an iris pattern in which the distribution pattern of inorganic pigments was problematic. We confirmed the depth and distribution pattern of pigments in the hydrogel. The results indicated that ultra-thin cryosectioning with TEM was effective for inspecting the distribution of inorganic substances in hydrogel-filled devices.